Trends in termination of pregnancy for neural tube defects in England and Wales from 2007 to 2017: Observational prospective study. (26th October 2021) - Allen, Ruth; James, Andrew; Sankaran, Srividhya
Abstract: Background/Objective: Neural tube defects (NTDs) affect approximately 300, 000 pregnancies worldwide each year. Many of these pregnancies are lost to miscarriage or termination of pregnancy. Here, we have analysed the trends of termination of pregnancy for NTDs from the national data for England and Wales. Methods: Data for all terminations for residents in England and Wales for the period of 2007–2017 were obtained through Health and Social Act 4 (HSA4) submitted to the Department of Health. Using the ICD‐10 codes, terminations for NTDs were selected for analysis. The statistical test Chi‐squared was performed using SPSS‐v25, where appropriate. Results: In the 11‐year period, there were 28, 866 terminations under Ground E; of which 4425 (15.33%) had a diagnosis of NTD. The number of NTD cases increased over the time period from 308 in 2007 to 517 in 2017 (67.9%). Significant results were also seen when analysing the relationship between ethnicity, gestation and terminations where an NTD was diagnosed. Conclusion: With the availability of routine prenatal ultrasound, the termination for NTDs is on the rise in England and Wales, in spite of the health advice of periconceptional folic acid. This study demonstrates the need for implementation of further programmes to increase public health awareness of folic supplementation and government initiation of fortification to reduce NTDs. Key points: What's already known about this topic? The aetiology of Neural tube defects (NTDs) is known to be a complex interaction of genetic and environmental factors. The relationship between the risk of NTDs and folate deficiency has been widely researched and is proven to significantly increase the risk of NTDs. Despite knowledge regarding prevention, NTDs remain highly prevalent in the UK and worldwide and continue to be a great public health burden globally. What does this study add? This was a large study, using national level data of which there have been no previous comparable studies. The large number of cases and variables analysed allowed for more accurate conclusions to be drawn. Statistical analysis was implemented, showing significant results in many areas.